2022
DOI: 10.1177/10668969221081741
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characteristics in Low Grade Fetal Adenocarcinoma of the Lung: Two Case Reports and Literature Review

Abstract: Background: Low-grade fetal adenocarcinoma of the lung is a rare pulmonary tumor resembling fetal lung histologically. Due to its rarity, there is limited information regarding the pathogenesis and biological characteristics of low-grade fetal adenocarcinoma of the lung. Here, we describe two cases of low-grade fetal adenocarcinoma of the lung treated at our hospital and summarize cases of low-grade fetal adenocarcinoma of the lung reported in the literature. Case presentation: We examined two cases (one woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…DICER1 hotspot-negative NSCLC cases harbored a typical mutational landscape of NSCLC, with the most frequently mutated genes being TP53, KRAS, STK11, CDKN2A and ARID1A, 17,22 whereas DICER1 hotspotpositive cases revealed a strong co-occurrence of CTNNB1 mutations compared with NSCLCs lacking DICER1 hotspots. CTNNB1 mutations have previously been reported in DICER1-associated WDFLACs, 2,15,18,23,24 PB 6,11,25 and rarely, PPB. 10,11 Beta-catenin IHC supported the CTNNB1 sequencing results showing nuclear positivity in 5/7 tumors that harbored a PV in CTNNB1 (4/5 hotspot-positive cases and 1/2 single variant cases), similar to a study by Nakatani et al, 25 which demonstrated nuclear positivity in all 4 cases of classic PB of which 3/4 harbored a CTNNB1 PVs.…”
Section: Discussionmentioning
confidence: 94%
“…DICER1 hotspot-negative NSCLC cases harbored a typical mutational landscape of NSCLC, with the most frequently mutated genes being TP53, KRAS, STK11, CDKN2A and ARID1A, 17,22 whereas DICER1 hotspotpositive cases revealed a strong co-occurrence of CTNNB1 mutations compared with NSCLCs lacking DICER1 hotspots. CTNNB1 mutations have previously been reported in DICER1-associated WDFLACs, 2,15,18,23,24 PB 6,11,25 and rarely, PPB. 10,11 Beta-catenin IHC supported the CTNNB1 sequencing results showing nuclear positivity in 5/7 tumors that harbored a PV in CTNNB1 (4/5 hotspot-positive cases and 1/2 single variant cases), similar to a study by Nakatani et al, 25 which demonstrated nuclear positivity in all 4 cases of classic PB of which 3/4 harbored a CTNNB1 PVs.…”
Section: Discussionmentioning
confidence: 94%